An Analysis and Evaluation toward the Implementation of Teacher Competency Test in Makassar, South Sulawesi, Indonesia - Rezki Ramdani; Muthia Mutmainnah Darmuh (Newinera Publisher, 2022)
The purpose of this research is to analyze and evaluate the Teacher Competency Test (TCT) implementation in Makassar, South Sulawesi, Indonesia. In addition, this research analyzed the perspectives of instructors, officer representatives, and academics on the TCT Objective and Implementation, as well as the Program's Effectiveness and Efficiency. This research used a qualitative approach and in-depth interviews. The results imply that the current TCT does not accurately reflect teachers' real-world proficiency owing to teachers' lack of computer literacy, since they were evaluated using a computer-based testing. However, the outcomes of this evaluation are also valuable for government decision-making on the mapping of teachers' requirements and future development. Second, the development of TCT program management and the quantity of financing for teacher training must be enhanced to assure the program's future viability. This research concludes by recommending a strategic shift to enhance student learning: mapping teachers' competency and education and the Sustainable Teachers Training and Development Program. Proper and ongoing professional development would not only assist instructors in supporting successful learning, but it would also enable experienced teachers to work with novice teachers and act as mentors for them, therefore enhancing classroom learning circumstances.